2020
DOI: 10.1002/cbf.3514
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of long non‐coding RNA RP11‐363E7.4 inhibits proliferation and invasion in gastric cancer

Abstract: LncRNA RP11-363E7.4 has been shown to be downregulated in gastric cancer (GC), while the effect of lncRNA RP11-363E7.4 on GC and its potential molecular mechanisms is unclear. The purpose of this study was to explore the functional role and underlying molecular mechanisms of lncRNA RP11-363E7.4 involved in GC progress. To address the question, quantitative real-time PCR assay was performed to confirm lncRNA RP11-363E7.4 expression levels in GC tissues and cell lines. Cell proliferation, apoptosis, migration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…12,13 For example, lncRNA RP11-363E7.4 inhibits gastric cancer cell proliferation and invasion. 14 LncRNA HAND2-AS1 suppresses liver cancer progression through inactivating the JAK-STAT signaling. 15 Importantly, the biological role and regulatory function of lncRNAs in CRC are also identified.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 For example, lncRNA RP11-363E7.4 inhibits gastric cancer cell proliferation and invasion. 14 LncRNA HAND2-AS1 suppresses liver cancer progression through inactivating the JAK-STAT signaling. 15 Importantly, the biological role and regulatory function of lncRNAs in CRC are also identified.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to be involved in fibrogenesis in idiopathic pulmonary fibrosis [ 79 ] and found to be dysregulated in patients with myocardial infarction and atrial fibrillation [ 80 , 81 ]. Furthermore, studies have reported its dysregulation in two colon carcinoma cell lines (SW480 and Caco2) upon knockdown of the aurora kinase A ( AURKA ) gene [ 82 ], in papillary thyroid carcinoma [ 83 ], in hepatocellular carcinoma treated with cisplatin [ 84 ], and in gastric cancer [ 85 , 86 ]. Another novel transcript ENSG00000272468 (also known as Lnc-HIST1H2BJ-3 ) [ 87 ] and MAP3K4-AS1 [ 88 ] were reported to be dysregulated in stomach adenocarcinoma and in breast cancer, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hub nodes of ferroptosis-related regulatory networks comprising four lncRNAs, five miRNAs, and one mRNA were identified, indicating their importance in regulating ferroptosis and implying their role as potential biomarkers or drug targets in patients with ALF. Among these ten hub nodes identified, RP11-363E7.4, miR-106a-5p, miR-3666, miR-665, miR-590-5p, and STMN1 facilitate cell death, whereas miR-4295 inhibits apoptosis in human glioma cell lines [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. miRNA-106a-5p, which is directly targeted by four other lncRNAs in the hub nodes, was sponged and downregulated in breast cancer cells, leading to inhibition of ferroptosis [ 65 ].…”
Section: Discussionmentioning
confidence: 99%